2021
DOI: 10.1111/jfbc.13856
|View full text |Cite
|
Sign up to set email alerts
|

Hypouricemia effects of corn silk flavonoids in a mouse model of potassium oxonated‐induced hyperuricemia

Abstract: The hypouricemic effect of corn silk flavonoids (CSFs) in vivo that were extracted by ethanol and fractionated by continuous elution with 40% (CSF‐A) and 60% (CSF‐B) ethanol solutions on polyamide column were investigated in this study. CSFs reduced serum uric acid (UA) level in a mouse model of potassium oxonate‐induced hyperuricemia. CSF‐B had the best hypouricemic effect, as it decreased the serum UA level by 26.69% and xanthine oxidase (XO) activity in the serum by 11.29%. The mechanism of action of CSF‐B … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 38 publications
0
17
0
Order By: Relevance
“…This suggests that hexoses in positions 3 and 4′ give a different pharmacological profile to kaempferol-3,4′-di- O -β-glucoside, since the treatment was remarkably effective intraperitoneally and one of the mechanisms involved was uricosuric. Previous studies [ 27 ] have suggested that the presence of hydroxyl groups at positions C3, C5, C7 and C-4′ of the chemical structure of flavonoids are important for XO-inhibiting and antihyperuricaemic activity. This theory may explain why kaempferol-3,4′-di- O -β-diglucoside showed no effect on hepatic xanthine oxidase activity.…”
Section: Resultsmentioning
confidence: 99%
“…This suggests that hexoses in positions 3 and 4′ give a different pharmacological profile to kaempferol-3,4′-di- O -β-glucoside, since the treatment was remarkably effective intraperitoneally and one of the mechanisms involved was uricosuric. Previous studies [ 27 ] have suggested that the presence of hydroxyl groups at positions C3, C5, C7 and C-4′ of the chemical structure of flavonoids are important for XO-inhibiting and antihyperuricaemic activity. This theory may explain why kaempferol-3,4′-di- O -β-diglucoside showed no effect on hepatic xanthine oxidase activity.…”
Section: Resultsmentioning
confidence: 99%
“…Also, compounds including naringenin, kaempferol, apigenin, luteolin, aesculin, orientin, hyperoside, diosmin, etc. were identified in the ethanolic extract of corn silk by hybrid-quadrupole-TOF LC/MS/MS, which may be responsible for its hypouricemic effect . A plethora of research studies illustrated the protective action of various phytocompounds that are identified by UPLC-MS in kidney-related disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Modern research shows that corn silk contains sugars, flavonoids, mineral elements, volatile oils, alkaloids, amino acids, and other chemical components that have anti-oxidant [47], antibacterial [48], antitumor [49], blood sugar-lowering [50], and other pharmacological effects. A recent study found that corn silk can reduce serum uric acid levels by 26.69% (p < 0.05) and serum xanthine oxidase (XO) activity by 11.29% (p < 0.05) [51]. In addition, a study found that corn silk extract suppressed plasma uric acid in high salt-fed rats (p < 0.05) [13].…”
Section: Discussionmentioning
confidence: 99%